Respiratory Mandibular Movement Signals Reliably Identify Obstructive Hypopnea Events During Sleep - Martinot, Jean-Benoit; Le-Dong, Nhat-Nam; Cuthbert, Valerie; Denison, Stephane; Borel, Jean C.; Gozal, David; Pépin, Jean L. (Frontiers in Neurology, 2019)
Context: Accurate discrimination between obstructive and central hypopneas requires quantitative assessments of respiratory effort by oesophageal pressure (OeP) measurements, which preclude widespread implementation in sleep medicine practice. Mandibular Movement (MM) signals are closely associated with diaphragmatic effort during sleep. Objective: We aimed at reliably detecting obstructive off central hypopneas events using MM statistical characteristics. Methods: A bio-signal learning approach was implemented whereby raw MM fragments corresponding to normal breathing (NPB; n= 501), central (n= 263) and obstructive hypopneas (n= 1861) were collected from 28 consecutive patients (mean age= 54 years, mean AHI= 34.7 n/h) undergoing in-lab polysomnography (PSG) coupled with a MM magnetometer, and OeP recordings. 23 input features were extracted from raw data fragments to explore distinctive changes in MM signals. A Random Forest model was built upon those input features to classify the central and obstructive hypopnea events. External validation and interpretive analysis were performed to evaluate the model’s performance and the contribution of each feature to the model’s output. Results: Obstructive hypopneas were characterized by a longer duration (21.9 vs 17.8 s, p<10-6), more extreme low values (p<10-6), more negative trend reflecting mouth opening amplitude, wider variation and asymmetrical distribution of MM amplitude. External validation showed a reliable performance of the MM features-based classification rule (Kappa coefficient = 0.879 and a balanced accuracy of 0.872). The interpretive analysis revealed that event duration, lower percentiles, central tendency and trend of MM amplitude were the most important determinants of events. Conclusions: MM signals can be used as surrogate markers of OeP to differentiate obstructive from central hypopneas during sleep.